Initial Energy for External Electrical Cardioversion of Atrial Fibrillation - Figueiredo,Edilberto (2002)
OBJECTIVE - To investigate the initial energy level required for electrical cardioversion of atrial fibrillation (AF). METHODS - We studied patients undergoing electrical cardioversion in the 1st Multicenter Trial of SOCESP. Patients were divided into 2 groups according to the initial energy level of electrical cardioversion: 100J and > or = 150J. We compared the efficacy of the initial and final shock of the procedure, the number of shocks administered, and the cumulative energy levels. RESULTS - Eight-six patients underwent electrical cardioversion. In 53 patients (62%), cardioversion was started with 100J, and in 33 patients (38%), cardioversion was started with > or = 150J. Groups did not differ regarding clinical features and therapeutical interventions. A tendency existed towards greater efficacy of the initial shock in patients who received > or = 150J (61% vs. 42% in the 100J group, p=0.08). The number of shocks was smaller in the > or = 150J group (1.5±0.7 vs. 2.1±1.3, p=0.04). No difference existed regarding the final efficacy of electrical cardioversion and total cumulative energy levels in both groups. In the subgroup of patients with recent-onset AF (<=48h), the cumulative energy level was lower in the 100J group (240±227J vs. 324±225J, p=0.03). CONCLUSION - Patients who were given initial energy of > or = 150J received fewer counter shocks with a tendency toward greater success than those patients who were given 100J; however, in patients with recent-onset AF, the average cumulative energy level was lower in the 100J group. These data suggest that electrical cardioversion should be initiated with energy levels > or = 150J in patients with chronic AF.